Promoting the Positive Thinking and Mindfulness Training for Autism Caregiver with Depression - Pinyo Itsarapong; Kotchapong Sarakan; Laddawan Arunyakanon (International Journal of Child Development and Mental Health, 2018)
Autism’s problematic behaviors and special care needed are large burdens to the family which might result in depression of caregivers. Positive thinking and mindfulness training can release depression. The purposes of this research and development were to 1) study the situation and related factors of depression among autism caregivers 2) develop and evaluate the model of positive thinking and mindfulness training for autism caregivers with depression. The study consisted of 2 phases including Phase I: analyzing situation and related factors of depression among autism caregivers by questioning and interviewing, Phase II: developing the model of positive thinking and mindfulness training for autism caregivers with depression. The quantitative data were analyzed using descriptive statistics, including Wilcoxon signed-rank test; the qualitative data were analyzed using content analysis. The results of Phase I study demonstrated that mothers of children with autism were more likely to suffer from depression than fathers and their ages were 37.54 years (SD = 8.21). Phase II, construction and development of the model of positive thinking and mindfulnesstraining consisted of 7 elements including: 1) optimistic, 2) belief, 3) commitment, 4) mindfulnessin everyday life, 5) basic meditation exercise, and 6) meditation exercises. After applying the model, caregivers of children with autism have the average scores of depression lower than before entering the model significantly (p <.05). The results of this study indicated that training which promotes the positive thinking and mindfulness in caregivers of children with autism can decrease depression. Further study on this model in other mental health settings is recommended.